Bit Error Rate (BER) Performance Analysis on ASK, FSK, and PSK Digital Modulation in AWGN Channels - Muhammad Ferdinand Putra Mulyadi; Rhaya Prayoga; Muhammad Rifqi Sardono; Rustamaji (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Digital communication systems face the challenge of Additive White Gaussian Noise (AWGN), which causes signal distortion and increases the Bit Error Rate (BER). This study aims to analyze and compare the BER performance of Amplitude Shift Keying (ASK), Frequency Shift Keying (FSK), and Phase Shift Keying (PSK) modulation techniques on AWGN channels through MATLAB simulations over an SNR range of 0–14 dB. A quantitative experimental approach was employed using Monte Carlo analysis with 100,000 bits sampled per SNR test point, validated against theoretical error probability using the Q function. The results demonstrate that PSK (BPSK) achieves the best performance, reaching a BER of  at an SNR of approximately 7 dB, while FSK requires approximately 10 dB to achieve the same BER threshold — a difference of ≈3 dB — and ASK remains at a BER of approximately  even at 14 dB SNR, reflecting its inherent vulnerability to additive amplitude noise. These findings confirm that PSK modulation offers the greatest power efficiency and noise robustness among the three techniques. The study recommends PSK for high-noise wireless applications such as IoT sensor networks and communication satellites where optimal power efficiency and transmission reliability are critical.